Inhibitory effect of curcumin on testosterone induced benign prostatic hyperplasia rat model. Issue 1 (December 2015) - Kim, Su; Seok, Hosik; Park, Hae; Jeon, Hye; Kang, Sang; Lee, Byung-Cheol; Yi, Jooil; Song, Sang; Lee, Sang; Kim, Young; Chung, Joo-Ho
Abstract Background Benign prostatic hyperplasia (BPH) is one of the common male diseases, which is provoked by dihydrotestosterone (DHT) and androgen signals. Several studies showed that curcumin has various effects of prevention and treatment to diseases. We investigated whether curcumin may repress the development of BPH in male Wistar rats. Methods Seven weeks male Wistar rats were and divided into 4 groups (normal group, BPH group, finasteride group, curcumin group;n = 8 for each group). In order to induce BPH in rats, rats were castrated and testosterone was injected subcutaneously everyday (s.c., 20 mg/kg). Rats in the curcumin group were treated 50 mg/kg, administered orally for 4 weeks. After 4 weeks, all rats were sacrificed and their prostate and serum were analyzed. Results Compared to the finasteride group as positive group, the curcumin group showed similarly protective effect on BPH in histopathologic morphology, prostate volume. Results of immunohistochemistry and western-blot showed decreased expressions of VEGF, TGF-ß1, and IGF1 were also decreased in the curcumin group. Conclusions These results suggested that curcumin inhibited the development of BPH and might a useful herbal treatment or functional food for BPH.